PATIENTS WITH POLYPOUS FORM OF ALLERGIC RHINOSINUSITIS AND BRONCHIAL ASTHMA (Modern American Journal of Medical and Health Sciences, 2025)
In recent years, the relationship and co-occurrence of perennial allergic rhinosinusitis (AR) and bronchial asthma (BA) have received significant attention worldwide. The relevance of this problem is due to many factors, the most significant of which are the high prevalence of the combination of year-round AR and BA, the virtually ubiquitous annual increase in the number of patients with this pathology, its significant impact on social activity and quality of life, and the significant financial costs associated with the treatment of this category of patients. Since the beginning of the study of the relationship between the upper and lower respiratory tract, it has been proven that they represent a single whole in structural and functional terms.